Genetic analysis of mixed models of fruit sugar–acid fractions in a cross between jujube (Ziziphus jujuba Mill.) and wild jujube (Z. acido jujuba) - Zhi, Yang; Chuanjiang, Zhang; Xinfang, Yang; Mengyi, Dong; Zhenlei, Wang; Fenfen, Yan; Cuiyun, Wu; Jiurui, Wang; Mengjun, Liu; Minjuan, Lin (Frontiers in Plant Science, 2023)
Chinese jujuba (Ziziphus jujuba), an economically significant species in the Rhamnaceae family, is a popular fruit tree in Asia. Jujuba fruit have considerably higher concentrations of sugar and acid than other plants. Due to the low kernel rate, it is extremely difficult to establish hybrid populations. little is studied about jujuba evolution, domestication, and especially the underpinnings of the sugar and acid components of the jujuba.Therefore, we used the cover net controlling as a hybridization technique to complete the cross-breeding of (Ziziphus jujuba Mill.) ‘JMS2’ and (Z. acido jujuba)‘Xing16’ to obtain an F1 population(179 hybrid progeny). Sugar and acid content of F1 and parent fruit were determined by HPLC. The coefficient of variation ranges from 28.4 to 93.9%. Sucrose and quinic acid had an increase compared to their parents. The population showed continuous distributions with transgressive segregation on both sides.Analysis by the mixed major gene and polygene inheritance model. Glucose is controlled by one additive-dominant major gene and polygenes. Malic acid is controlled by two additive-dominant major genes and polygenes, and oxalic acid and quinic acid are controlled by two additive-dominant-epistatic major genes and polygenes and study the combining ability and genetic parameter. The results of this study provide insights into the genetic predisposition and molecular mechanisms of sugar-acid in jujuba fruits